Denda dalam Keadaan Kahar Akibat Wanprestasi pada Perjanjian Pengangkutan - Andrian Fauji Silalahi; I Made Kantikha (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
The relationship between the two legal subjects who entered into an agreement resulted in the emergence of a bond in the form of rights and obligations of both parties to an achievement, for that coal transportation agreement from South Kalimantan to Belawan - Medan which should be scheduled on May 16 - 19, 2017, but in reality from May 19 - 23, 2017 there was a Force Majeure in the form of a major flood which resulted in the inability to carry out Haulinng activities (Coal Transportation), thus making the issuance of a fine for breach of contract by imposing Demurrage fees. In this study, the formulation is how a lawsuit for breach of contract can occur in a coal shipping agreement in a force majeure situation and how the judge's decision is considered regarding the determination of unilateral fine sanctions in force majeure in a coal shipping agreement from Kalimantan to Medan. This study is also useful for analyzing the criteria for breach of contract in force majeure in a coal shipping agreement and for analyzing the resolution of the determination of unilateral fine sanctions in force majeure in a coal shipping agreement from Kalimantan to Medan. Which in this study uses a normative juridical research method. According to the theory of justice, if the force majeure event can be proven by only one party with evidence that cannot be denied, then both parties are obliged to set aside/ignore the agreement first until the force majeure can be resolved. Therefore, it can be concluded that the Judge's consideration is also in line with the application of the force majeure clause, but the fines submitted by the Panel of Judges still impose fines on both parties because both have suffered losses.